Pengaruh Budaya Perusahaan Terhadap Motivasi Kerja Dan Dampaknya Pada Kinerja Karyawan - Vira Aulia Sabrina,; Dwi Utami,; Sayed Haikal Fuad, (Jurnal Mutiara Ilmu Akuntansi, 2023)
The purpose of this study is to determine the effect of corporate culture on work motivation and its impact on employee performance. This study uses a conceptual method, the authors get the results that corporate culture and work motivation as dependent variables have a significant influence on employee performance which acts as an independent variable. This is because corporate culture has a positive and significant effect on work motivation, where a stronger corporate culture will provide direction and values for employees in the company to carry out tasks and work, so that employee performance will increase. Corporate culture has a positive relationship with employee performance. With a corporate culture, employee performance will increase. A strong corporate culture can help employee performance and company performance, because it will create something extraordinary in employees.